ANTIBACTERIAL ACTIVITY AGAINST ORAL PATHOGENS AND HEMOLYTIC PROPERTIES FROM KAPPAPHYCUS SP SEAWEED EXTRACT - Karunya Arumugam, Dr. Abirami Arthanari, Dr. Sivaperumal, (Chelonian Research Foundation, 2023)
INTRODUCTION:Kappaphycus is a genus of red seaweed that belongs to the family of Areschougiaceae. The species within the Kappaphycus genus are commonly found in tropical and subtropical regions, particularly in the Indian and Pacific Oceans.The seaweed extract obtained from Kappaphycus species, particularly Kappaphycus alvarezii, has gained attention in various fields due to its diverse bioactive compounds and potential applications. Kappaphycus species have been recognized for their rich bioactive compounds, including polysaccharides, peptides, and secondary metabolites, which exhibit diverse biological activities. Kappaphycus seaweed extract contains high levels of carrageenan, a hydrocolloid widely used in the food industry as a gelling, thickening, and stabilizing agent.This species has various Biomedical and Pharmaceutical Applications and environmental applications . It also possesses Anti-tumor and Anti-cancer Effects.The antibacterial activity of Kappaphycus seaweed extract against oral pathogens suggests its potential application in oral care products, such as mouthwashes or toothpaste formulations, as a natural alternative or adjunct to conventional antimicrobial agents. The aim of this study is to analyze the Antibacterial activity against oral pathogens and hemolytic properties from kappaphycus sp seaweed extract. AIM: To determine the Antibacterial activity against oral pathogens and hemolytic properties from kappaphycus sp seaweed extract. MATERIALS AND METHODS: The seaweed samples of the plant kappaphycus alvarezi was collected and the seaweed extract was prepared.Antibacterial assays and hemolytic assays were done to find the antibacterial and hemolytic properties of the extract. RESULTS:The production of antimicrobial activity was considered to be an effective indicator of the capability of the seaweeds to synthesize bioactive secondary meta- bolites. Gram positive bacteria were more susceptible to crude extract of seaweed than Gram negative bacteria.The extract showed good hemolytic activity as well . CONCLUSION: In conclusion, the study on the antibacterial activity against oral pathogens and hemolytic properties of Kappaphycus sp seaweed extract has provided valuable insights into the potential of this natural extract as an antimicrobial agent for oral care applications. The extract has demonstrated significant antibacterial activity against oral pathogens, making it a promising candidate for combating oral infections. Additionally, the extract has shown negligible hemolytic properties, indicating its potential safety for oral use. KEYWORDS: kappaphycus sp , antimicrobial assay , hemolytic assay, oral pathogens , Seaweed extract.